Exploring the prognostic impact of tumor sidedness in ovarian cancer: A population-based survival analysis of over 10, 000 patients. (2022) - Bairi, Khalid El; Trapani, Dario; Page, Cécile Le; Saad, Anas; Jarroudi, Ouissam Al; Afqir, Said
Highlights: There is emerging evidence suggesting that the laterality concept might also be applied to ovarian cancer. Our SEER-based study demonstrated that the impact of tumor sidedness has no prognostic implication in ovarian cancer (right vs left). Bilateral ovarian carcinomas at diagnosis might be marginally more associated with unfavorable outcomes. Abstract: Very recently, emerging evidence demonstrated that laterality might be an independent prognostic factor in patients with advanced ovarian cancer (OC). Based on preliminary provocative observations, our study aimed to investigate the prognostic impact of sidedness in a large cohort of women with OC. Survival was estimated based on Kaplan-Meier method and survival curves were compared using Log-rank test. Cox proportional-hazards model was used to study the association between survival and covariates. A total of 10, 177 women with OC were included. Mean age at diagnosis was 59.58 years (±13.5); 36.7% OC right-sided, 36.9% were left- sided, and 26.4% had bilateral OC. The median overall survival (OS) for the entire population was 77 months, with the lowest median OS observed in bilateral OC (median OS: 34 months). The prognostic value of OC sidedness was not confirmed at the univariable analysis (HR = 0.958; 95% CI: 0.888–1.033, p  = 0.268). However, women with bilateral OC has a 45% higher risk of death as compared with unilateral diagnosis (HR = 1.453; 95% CI: 1.410–1.497; p < 0.001). The independent prognostic value was further confirmed on multivarible analysis after adjusting for covariates including age, marital status, histological type, CA-125 at diagnosis, grade, stage, chemotherapy and surgery (HR = 1.087; 95% CI: 1.043–1.136, p  = 0.02). However, the ultimate prognostic significance appeared less prominent, with bilateral OC conferring a relative increase of 8.7% of mortality. Our real-world study demonstrated that impact of tumor sidedness has no prognostic implication (right vs left OC) but bilateral OCs might be marginally more prognostically unfavorable. Prospective validation might be warranted, to confirm the prognostic significance of OC sidedness, including for the presence of key genetic alterations and lymph nodes asymmetry, to better stratify patients with OC and predict outcomes according to tumor sidedness at diagnosis.